Assay of Serum Glutamic-Oxaloacetic Transaminase Using Malate Dehydrogenase Preparation Obtained from Streptomyces aureofaciens - Yamanaka, H.; Laluce, C.; Deoliveiraneto, G. (Marcel Dekker Inc, 1995)
A modified spectrophotometric method for serum glutamic-oxaloacetic transaminase (SGOT) assay was developed. A crude cell-free extract from Streptomyces aureofaciens which showed a high level of malate dehydrogenase (MDH) activity (E.C. 1.1.1.37) was used as the enzymatic indicator. The lyophilized microbial preparation was used without previous purification and was quite stable under refrigeration for one year. Serum sample assays using both the method utilizing the crude cell extract and an enzymatic commercial kit showed good correlation.
Keywords: TRANSAMINASE; SGOT; MALATE DEHYDROGENASE; STREPTOMYCES